ChemInform Abstract: Bismuth(III) Triflate‐Catalyzed Tandem Cyclizations Towards Complex Polycyclic Ethers. Issue 50 (November 2016) - Ondet, Pierrick; Lempenauer, Luisa; Dunach, Elisabet; Lemiere, Gilles
Abstract: Under bismuth(III) triflate catalysis, α‐hydroxy enol ethers with a tethered olefinic double bond undergo a double cyclization forming bridged polycyclic compounds with an additional oxaspirocycle.